Analysis of optimal operating modes of the induction traction drives for establishing a control algorithm over a semiconductor transducer - Liubarskyi, Borys; Petrenko, Аleksandr; Shaida, Viktor; Maslii, Artem (Eastern-European Journal of Enterprise Technologies, 2017)
The study addresses determining optimal operating modes of the induction traction drive. We identified optimal operating modes of the autonomous voltage inverter at different temperatures of windings of the traction motors for a tram carriage and a diesel locomotive. The identification is carried out of optimal parameters in the operating modes of autonomous voltage inverter of the traction drive of a tram and a diesel locomotive. We obtained dependences of performance efficiency and electromagnetic torque of the induction traction motor on the rotation frequency and temperature of the windings for the following modes: acceleration, recuperative braking, and maintaining preset speed. We determined operating modes of induction traction drive of the tram Tatra T3 VPA and the diesel locomotive 2TE25A over the entire range of motors' rotation frequency at spatial-vector and one-time pulse-width modulation of the semiconductor inverter for different values of temperature of the motor's windings. A technique was devised for this purpose, which is based on solving a problem on the optimization of parameters of the traction drive using a combined method that employs genetic algorithms and the Nelder–Mead method. It was established that dependences of change in the transition point from the spatial-vector to the one-time PWM on the temperature of traction motor for a tram and a diesel locomotive are not similar. Different level of the location of this point is predetermined by the different load in magnetic circle of the motor, by different level of saturation coefficient. The difference in saturation coefficient is 0.15‒0.4 r.u.